Evaluation of genetics of cancer predisposition in patients and efficacy of various chemotherapeutic drugs in Bangladesh - Hossain, Safa Binte (2019)
This project report is submitted in partial fulfilment of the requirements for the degree of Bachelor of Pharmacy, 2017.